Assessment and management of bone health in women with oestrogen receptor‐positive breast cancer receiving endocrine therapy: position statement summary. Issue 5 (18th July 2019) - Grossmann, Mathis; Ramchand, Sabashini K; Milat, Frances; Vincent, Amanda; Lim, Elgene; Kotowicz, Mark A; Hicks, Jill; Teede, Helena J
Abstract: Introduction: Representatives appointed by relevant Australian medical societies used a systematic approach for adaptation of guidelines (ADAPTE) to formulate clinical consensus recommendations on assessment and management of bone health in women with oestrogen receptor‐positive early breast cancer receiving endocrine therapy. The current evidence suggests that women receiving adjuvant aromatase inhibitors and pre‐menopausal woman treated with tamoxifen have accelerated bone loss and that women receiving adjuvant aromatase inhibitors have increased fracture risk. Both bisphosphonates and denosumab prevent bone loss; additionally, denosumab has proven anti‐fracture benefit in post‐menopausal women receiving aromatase inhibitors for hormone receptor‐positive breast cancer. Main recommendations: Women considering endocrine therapy need fracture risk assessment, including clinical risk factors, biochemistry and bone mineral density measurement, with monitoring based on risk factors. Weight‐bearing exercise and vitamin D and calcium sufficiency are recommended routinely. Anti‐resorptive treatment is indicated in women with prevalent or incident clinical or morphometric fragility fractures, and should be considered in women with a T score (or Z score in women aged < 50 years) of < − 2.0 at any site, or if annual bone loss is ≥ 5%, considering baseline bone mineral density and other fracture risk factors. Duration of anti‐resorptive treatment can be individualised based on absolute fracture risk. Relative to their skeletal benefits, risks of adverse events with anti‐resorptive treatments are low. Changes in management as result of the position statement: Skeletal health should be considered in the decision‐making process regarding choice and duration of endocrine therapy. Before and during endocrine therapy, skeletal health should be assessed regularly, optimised by non‐pharmacological intervention and, where indicated, anti‐resorptive treatment, in an individualised, multidisciplinary approach.